The Use of Situational Context in Predicting the End of the Comic Story - Erna Dwinata (STKIP PGRI TULUNGAGUNG, 2015)
There are many advantages offered by the use of comics as a medium of teaching language instruction . Sometimes this graphic novel can convey a better idea than a conventional one. Comics is a communication miniature between the reading and the author thatÂ is embed at the the characters of the author. Comic also hasÂ a field, tenor and mode. Those element are needed on the anylis of situational content. This article is to describe how the texts of the comic are analyzed using situational context